The Development of Social Services and Deinstitutionalization – a New Trend or a Permanent Shift in Aid for Dependent Individuals - Łuszczyńska, Maria (Niepełnosprawność i praca: Wymiary, konteksty, perspektywy, 2024)
The article attempts to show the actual scope of deinstitutionalization in comparison with the trends in the development of social services. The text aims to address the issue of understanding deinstitutionalization, the importance of social services and forecasting the directions in which welfare care systems for dependent people will go. The genesis of deinstitutionalization, the legal aspects of its presence in the discourse on social policy, as well as the specificity of services for people who are recognised as depended and their families will be presented, along with an attempt to show the perspective of actions for the coming years. The article is intended to be a contribution to further discussion on support for dependent people – through institutional and/or service support.